When Dyspnea Is More Than Pneumonia: Interwoven Mechanisms Of Autoimmune Multiorgan Disease In An Adolescent—A Case Report - Karina Cahya Widati (Riviera Publishing, 2025)
Dyspnea in adolescents is often underestimated as a simple respiratory infection, yet it may represent the fairst sign of complex autoimmune multiorgan disease. This report highlights the autoimmune mechanisms underlying dyspnea to promote early recognition of autoimmune disease in adolescents. An 18-year-old female presented with acute worsening of chronic dyspnea. She was tachypneic hypertensive, hypoxemic, and severe anemia. Examination revealed pallor, edema, basal fine crackles, and gallop. Laboratory findings showed renal impairment with proteinuria and hematuria. The albumin was normal and blood gas indicated respiratory alkalosis with compensatory metabolic acidosis. Infectious work-up revealed yeast-like fungi and mixed gram-positive cocci/gram-negative bacilli, while GeneXpert MTB was negative. Chest radiograph demonstrated pulmonary edema with pneumonia. Electrocardiography showed sinus tachycardia 119 bpm with right axis deviation and right ventricular hypertrophy. Echocardiography revealed right atria and ventricle enlargement, moderate tricuspid regurgitation, mild pericardial effusion, intermediate pulmonary hypertension, and preserved EF 64%. ANA test was positive, but performed only at discharge before referral for definitive immunological workup. The patient's life-threatening multiorgan dyspnea could be concluded as four major mechanisms, such as : 1) Renal & Volume Overload; 2) Cardiopulmonary Vasculopathy; 3) Autoimmune and Infectious Pulmonary Damage; 4) Severe Anemia. The profound multiorgan involvement and severe systemic inflammation provided a strong clinical rationale for highly active systemic autoimmune disease (SAID), most probable being Systemic Lupus Erythematosus. This case illustrates how adolescents' dyspnea with complicated systemic symptoms deserves an early diagnosis of autoimmune disease without waiting for infectious exclusion, to prevent the devastating consequences associated with diagnostic latency and delayed targeted intervention. As life-threatening dyspnea in an adolescent may be the catastrophic initial presentation of Probable Systemic Lupus Erythematosus.